Strategi efektif pemasaran digital untuk mengoptimalkan potensi bisnis umkm: Studi kasus amizza official - Istianah, Nur (Maliki Interdisciplinary Journal, 2025)
This research aims to identify the most relevant digital marketing methods to enhance Amizza Official’s visibility and competitiveness in the local market. The methods used include literature review, direct observation, and interviews with business owners. SWOT analysis and comparative studies of digital marketing strategies were applied. The research results indicate that the use of social media, particularly Instagram, plays a significant role in market expansion. The conclusion is that targeted and innovative digital marketing strategies can significantly improve MSME business performance. The recommendations from this study emphasize the importance of consistency in content creation, utilization of interactive features such as Instagram Story and Reels, and collaboration with local influencers to increase engagement. In addition, integration between social media and marketplaces is also recommended to accelerate the conversion from promotions to sales. In the future, Amizza Official is advised to continue to monitor digital marketing trends and conduct regular evaluations of the effectiveness of the strategies implemented, in order to be able to adapt to changing market dynamics.